Efektivitas Latihan Beban Metode Circuit Weight Training Terhadap Penurunan Berat Badan Dan Persentase Lemak Pada Member Fitness - Nugraha, Faizal Eka (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the effectiveness of weight training using the circuit weight training method on reducing body weight and body fat percentage among fitness members. Excess body weight and high body fat percentage are critical issues in fitness, as they affect both physical health and psychological well-being. The research method employed was an experimental design with a two-group pretest-posttest model. The sample consisted of 20 male and female fitness members aged 17–35 years, selected through purposive sampling. The treatment group participated in a circuit weight training program three times per week for eight weeks, with an intensity of 50% of 1RM, 15–20 repetitions, and 3–4 sets per session. Body weight was measured using a digital scale, while body fat percentage was assessed with a skinfold caliper at several anatomical sites. The results revealed a significant decrease in both body weight and body fat percentage after completing the circuit weight training program compared to baseline measurements. Statistical analysis confirmed that circuit weight training is effective in improving body fitness through the reduction of fat composition and excess weight. These findings suggest that circuit weight training can serve as an appropriate alternative training method in weight loss programs within fitness centers.